Meningkatkan Pemahaman Masyarakat Atas Hak-Hak Konsumen - Teng Berlianty; Agustina Balik; Ronald Fadly Sopamena (AIWADTHU: Jurnal Pengabdian Hukum, 2022)
Introduction: Community service through counseling in Rumberu Village, Inamosol District, West Seram Regency regarding public understanding of consumer rights on October 21, 2021.Purposes of Devotion: This activity aims to increase public understanding of consumer rights so that the people of Rumberu village not only know but also understand their rights as consumers which are protected by law. Method of Devotion: The service is carried out using the lecture method by each presenter in turn. Then the public will be invited to ask questions and they will be answered in turn by the presenters.Results of the Devotion: Through service activities with the title "Increasing Public Understanding of Consumer Rights", the people of Rumberu Village, Inamosol District, West Seram Regency became more aware of consumer protection laws and more specifically, this activity resulted in an understanding of community rights as consumer.